Distribution patterns in generalized vitiligo. (8th May 2013) - Speeckaert, R.; van, N.
Abstract Background Vitiligo is a common pigmentation disorder affecting approximately 1% of the world population. Nonetheless, its distribution pattern is not well investigated. Objective The aim of this study was to investigate whether the distribution pattern of vitiligo is dependent on the clinical characteristics. Methods A total of 700 generalized vitiligo patients were included in this retrospective observational cohort study. Results The most important predilection areas were the face (87%), followed by acral areas (76.3%) and extremities (59.7%). In women, joints (P = 0.002) (especially elbows), hips (P < 0.001), trunk (P < 0.001) and body folds (P < 0.001) (especially axillas) were more frequently affected compared to men. In contrast, in men more depigmentations in the beard area and genital area were observed (P < 0.001). Vitiligo at a young age is more prone to be localized at the lower extremities whereas the upper extremities are more susceptible at an older age. In the face, the periocular area is linked to a younger age, in contrast to the perioral area. Acral areas were more frequently affected in patients with autoimmune disorders (in particular thyroid disease) (P = 0.001). Conclusion These results point to important differences in the distribution pattern according to the clinical characteristics. Although in some of these areas Koebner's phenomenon probably plays a role, other differences may represent a specific characteristic vulnerability related to the age, gender or typical association with autoimmune disease.